Driven to the Bottle: Work- Related Risk Factors and Alcohol Misuse Among Commercial Drivers. (April 2015) - Bamberger, Peter A.; Cohen, Ayala
This study examines the role of workplace risk factors associated with stress, social availability, and policy enforcement in explaining the severity of alcohol misuse among truck and bus drivers. Using a sample of 227 commercial (i.e., bus and truck) drivers drawn randomly from the employees of eight Israeli transportation enterprises, findings indicate that less than 6% of drivers engage in hazardous drinking, with a far smaller proportion engaging in more risky forms of misuse (i.e., harmful or dependent drinking). Key work-related factors associated with the severity of drivers' alcohol misuse include the perception of permissive coworker drinking norms, role conflict, and supervisory abuse. Consistent with tension relief models of alcohol misuse, felt strain mediated the association between driver stressors and the severity of alcohol misuse. Perceptions of coworker drinking norms moderated the associations between stressors and supervisory monitoring (on one hand) and alcohol misuse (on the other). Implications for theory and practice are discussed.